An Analysis of Teachers Questioning Strategy During the Classroom Interaction in EFL Classroom - Aini, Nurul; Islamia, Ninda Shohwatul; Amanati, Atika Arribah (Indonesian Journal of Multidisciplinary Educational Research, 2023)
Each teacher has their own way of delivering questions called teacher asking strategies. This research aims to determine the different kinds of teacher questions used the teacher during the classroom interaction in EFL classroom. The method in this research uses qualitative descriptive. This purpose of the study is to analyze teacher questioning strategies that are utilized by English teachers in classroom interactions and the aim of these strategies, was described by researchers using qualitative descriptive methods. The instrument used in this research was an interview with a question count of 4 items. The participants of this research were 2 different English teachers. The results of this research show that question controlling strategy are often used by teachers to manage classes and question planning strategies are the least used methods to assess students' comprehension of the material presented.